Pengaruh Beban Kerja dan Work Life Balance terhadap Kepuasan Kerja Pegawai pada Balai Pemasyarakatan Kelas 1 Makassar - Adra Ayu Ningsih; Agung Widhi Kurniawan; Rezky Amalia Hamka; Romansyah Sahabuddin; Burhanuddin Burhanuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research is grounded in the understanding that employees are the core of organizational sustainability, and their job satisfaction is shaped not only by daily tasks but also by the organization’s ability to manage workload and support balance between work demands and personal life. This study aims to analyze the effect of workload and work-life balance on employee job satisfaction at the Class I Correctional Center (Bapas) Makassar. Using a quantitative approach, data were collected through questionnaires distributed to 54 employees and analyzed using multiple linear regression assisted by SPSS Statistics 25. The research variables consist of workload and work-life balance as independent variables, and job satisfaction as the dependent variable. The findings indicate that workload has a positive and significant effect on job satisfaction, suggesting that employees’ perception of being able to complete tasks effectively can increase their comfort and confidence at work. Work-life balance also shows a positive and significant influence, indicating that the ability to manage both work responsibilities and personal life contributes directly to greater feelings of satisfaction, stability, and motivation in performing duties. Simultaneously, both variables significantly affect job satisfaction, emphasizing the importance for organizations to regulate workload proportionally while providing space for employees to maintain a healthy life balance. These findings highlight that effective workload management and support for work-life balance are crucial organizational investments to foster a healthy, productive, and employee-centered work environment.